Use of active aggregates in concrete as a guarantee of expansion of raw material base and reduction of cost of products - Kovalchuk, O.; Zozulunets, V. (Ways to Improve Construction Efficiency, 2021)
Traditional natural materials (mainly granite and quartz) are usually used as aggregates for the manufacture of concrete products and structures. This raw material is tested, reliable and does not cause destruction during operation of structures. However, it is exhaustive and characterized by high cost. That is why it is advisable to consider the use of reactive (active) aggregates. Especially if you consider ways to eliminate alkaline corrosion. The development of alkaline concrete compositions with the use of active aggregates is the key to expanding the raw material base for the manufacture of building materials with a reduction in production costs compared to products based on traditional systems. The use of active mineral additives allows to reduce the content of free alkalis in the system, preventing the alkaline corrosion of hardened artificial stone. Simultaneously. the processes of interaction of the active siliceous component with alkalis in the cement system can be transferred from the category of destructive (such as destroying the structure of hardened stone) in constructive processes (binding these components into insoluble compounds during hydration and cement formation, without breaking its fixed structure and sealing material). Studies have shown the high efficiency of the proposed approaches for the binding of excess alkalis (more than 0.6%) and targeted synthesis of alkaline aluminosilicate-type tumors in the composition of artificial cement stone. At the same time, the issue of extending the results to control the formation of structures at different levels of concrete with the use of general construction cements requires further research, and the issue of stopping alkaline corrosion of hardened concrete has not been raised and is innovative from the point of view of domestic and world science.